LRP1/CD91 is up‐regulated in monocytes from patients with haemophilia A: a single‐centre analysis. (6th February 2013) - Franchini, M.; Urbani, S.; Amadei, B.; Rivolta, G. F.; Perna, C. Di; Riccardi, F.; Frattini, F.; Crestani, S.; Bonfanti, C.; Formentini, A.; Quintavalla, R.; Tagliaferri, A.
Summary The low‐density lipoprotein receptor‐related protein 1 (LRP1) is an ubiquitously expressed endocytic receptor that, among its several functions, is involved in the catabolism of coagulation factor VIII (FVIII) and in the regulation of its plasma concentrations. Although LRP1/CD91 polymorphisms have been associated with increased FVIII levels and a consequent thrombotic risk, no data are available on LRP1/CD91 expression in patients with inherited FVIII deficiency. With the aim of elucidating this issue, 45 consecutive patients with haemophilia A (HA) (18 severe, 5 moderate and 22 mild HA) were enrolled in this cross‐sectional, single‐centre survey. The LRP1/CD91 mean fluorescence intensity (MFI) in monocytes from HA patients was significantly higher than that detected in 90 healthy blood donors (105 vs. 67, P < 0.001). This over‐expression was independent of hepatitis C virus infection status and varied according to the severity of the haemophilia, being higher in patients with more severe FVIII deficiency. In conclusion, our study documents for the first time that LRP1/CD91 is over‐expressed on monocytes from HA patients, with the intensity of expression varying according to the severity of the FVIII deficiency. Further studies are needed to assess the clinical implications of these findings.